The Effect of PBL (Problem Based Learning) Method in Increasing Knowledge about Stroke Nursing Care in Students - Saragih, Ice Septriani; Saragih, Helinida; Barus, Mardiati (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nursing care is a systematic, structured and integrative nursing process in nursing science so that it is necessary to apply the PBL (Problem Based Learning) learning method, especially for stroke patients who have increased from year to year. The objective of this study is to determine the effect of the PBL method in increasing knowledge about stroke care in Sekolah Tinggi Santa Elisabeth Medan students Method: The method used is a quasi-experimental design with pre-post design. The number of samples in this study was 70 people. The sampling technique used was non-probability sampling with a purposive sampling approach with the inclusion criteria being level III students and those who had passed the adult nursing course. There were two research instruments used in this study, namely guidelines for implementing the PBL method and a student knowledge questionnaire about stroke nursing care. Data analysis used to compare differences in student knowledge before and after the intervention is using paired t test statistical analysis and will be presented in the form of a t test table. The results of study show that there is an influence of PBL on students' knowledge about stroke management (α=0.001). The results of the study show that there is an influence of PBL on increasing students' knowledge.